2018
DOI: 10.1021/acsnano.8b02867
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Semiconductor Nanosprings for Tunable Chiral Nanophotonics

Abstract: The search for the optimal geometry of optically active semiconductor nanostructures is making steady progress and has far-reaching benefits. Yet the helical springlike shape, which is very likely to provide a highly dissymmetric optical response, remains somewhat understudied theoretically. Here we comprehensively analyze the optical activity of semiconductor nanosprings using a fully quantum-mechanical model of their electronic subsystem and taking into account the anisotropy of their interaction with light.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Referring to the orbital distribution in the CsPbBr 3 nanocluster 38 , the locations of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) around Pb and Br atoms indicate that the screw dislocation among Pb-Br crystals may result in significant optical activity. By this inference, the origins of the CD signal come from the screw orbital geometry-induced electron scattering, as discussed in many studies [39][40][41] .…”
Section: Resultsmentioning
confidence: 88%
“…Referring to the orbital distribution in the CsPbBr 3 nanocluster 38 , the locations of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) around Pb and Br atoms indicate that the screw dislocation among Pb-Br crystals may result in significant optical activity. By this inference, the origins of the CD signal come from the screw orbital geometry-induced electron scattering, as discussed in many studies [39][40][41] .…”
Section: Resultsmentioning
confidence: 88%
“…Tandem measurements in which the chirality of the sensitizer matches the polarization preference of a chiral film may further enhance spin-injection efficiencies. Theoretical and experimental works are pointing to other ways of controlling light–matter interactions with strong dissymmetric optical responses, and the parameters important for spin filtering in chiral films are becoming apparent. , The marriage between these two fields to create more efficient spin injectors is currently in progress.…”
Section: Chiral Optoelectronic and Spintronic Applicationsmentioning
confidence: 99%
“…For example, it was shown that quartz, β-AgSe, α-HgS, selenium and tellurium crystals have chiral crystal structure and corresponding NCs have two enantiomers [37][38][39]. (ii) Chiral NP shape: NCs of intrinsically achiral materials may be grown in a chiral shape, e.g., twisted CdTe nanoribbons [40][41][42], nanosprings [43], nanoscrolls [44][45][46], plasmonic and semiconductor gammadions [47,48] and other chiral shapes [49,50]. (iii) Chiral assembly: achiral NPs may be assembled in chiral superstructures, e.g., DNA has been used to assemble NPs in helixes [51,52] and chiral "molecules" can be fabricated from coupled achiral semiconductor NCs [53,54].…”
Section: Introductionmentioning
confidence: 99%